Post a New Question

Math - algebra

posted by on .

Find both solutions to the equation:

q(squared) - 6q + 5 = 0

  • Math - algebra - ,

    doesn't it factor

    (q-1)(q-5)=0

  • Math - algebra - ,

    let's say q = 10

    (10 -1) (10-5) = 0
    (9)(5) = 45

    I'm not trying to be a problem, it's been more years than I'd like to admit since I've done this, and I'm trying to help my son with homework. He's trying to "work backwards" to solve this, and he thinks he can do this:
    q(squared) - 6q + 5 = 0
    q(sq) - 6q = -5
    then he wants to just divide the 6q on the left side by the 6, as well as the -5 getting:
    q(sq)= -.83 (he's leaving out the other q)

  • Math - algebra - ,

    I've got your factoring thing - do you have a 2nd solution?

  • Math - algebra - ,

    wouldn't factoring it make it look like this?

    q(q-6)+ 5 = 0

  • Math - algebra - ,

    yes, but that is of no use. Recheck my factors, and solve for the roots.

  • Math - algebra - ,

    Hi,

    i'm not a math expert, just another dad trying to help my kid.
    i found this and thought it might help.

    oops, guess i can't paste a website address here. if you google quadratic equation calculator it should come up

    i think using the quadratic equation here might the way to go?

    came up with 5 or 1 as the answer.

    hope this helps more than confuses

  • Math - algebra - ,

    i think it would be
    q(sq)-6q+5=0
    or,q(sq)-5q-q+5=o
    or,q(q-5)-1(q-5)=0
    or,(q-5)(q-1)=0
    either,q=5 or,q=1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question